Academic Literacy and Student Diversity: Evaluating a Curriculum-Integrated Inclusive Practice Intervention in the United Kingdom - Calvo Martínez, Sara; Celini, Luciano; Morales Pachón, Andrés; Guaita Martínez, José Manuel; Núñez-Cacho Utrilla, Pedro (Sustainability, 2020)
The sustainability of universities is based, among other aspects, on their ability to adapt to changes and the needs of students, an increasingly diverse population. In this sense, Academic literacy provision at universities tends to be centralized and to offer language support for general academic literacy purposes rather than language development that responds in a more nuanced way to the particular literacy needs of students' disciplines. Yet, in recent years, several studies have supported the integration of academic literacy into subject teaching outlining the principles of an inclusive model of academic literacy instruction. This paper draws on a theoretical framework developed by Wingate to evaluate a curriculum-integrated inclusive practice intervention in the United Kingdom with students from a first-year credit-bearing module at Middlesex University Business School. The study used a mixed methods approach that includes a literature review, secondary data, feedback questionnaire and a focus group to evaluate our teaching method and reflect on the collaboration of the team members to develop this inclusive pedagogical approach. The findings suggest that, on the whole, this intervention was perceived by both the module teaching team and students as positive, welcoming and often crucial for supporting undergraduate students into the disciplinary discourse of their subject of study. Yet, recommendations were made with respect to developing better guidelines for subject lecturers on how to deliver the integrated academic literacy as well as the importance of the participation of students, student learning assistants and graduate teaching assistants in the design of the intervention. This study contributes to the literature on inclusive practice intervention and pedagogical approaches to integrating academic literacy into subject teaching for a diverse student population, contributing to the social sustainability of the universities.
Keywords: academic literacy; curriculum-integrated design; inclusive practice intervention; student diversity; Scopus; JCR